Easy Language Research Text and User Perspectives - Hansen-Schirra, Silvia; Maaß, Christiane (Easy - Plain - Accessible, 2020)
This volume presents new approaches in Easy Language research from three different perspectives: text perspective, user perspective and translation perspective. It explores the field of comprehensibility-enhanced varieties at different levels (Easy Language, Plain Language, Easy Language Plus). While all are possible solutions to foster communicative inclusion of people with disabilities, they have varying impacts with regard to their comprehensibility and acceptability. The papers in this volume provide insights into the current scientific activities and results of two research teams at the Universities of Hildesheim and Mainz and present innovative theoretical and empirical perspectives on Easy Language research. The approaches comprise studies on the cognitive processing of Easy Language, on Easy Language in multimodal and multicodal texts and different situational settings as well as translatological considerations on Easy Language translation and interpreting.